Self-regulation, metacognition and child- and adult-initiated activity: does it matter who initiates the task?. Issue 5 (3rd May 2016) - Robson, Sue
Abstract : Debate about the balance between child- and adult-initiated activities in early childhood settings is long standing. This article reports a study of 29 children aged 4–5 years in a London state school, on the influences of child- and adult-initiated activities on children's self-regulation and metacognition. Whilst both contexts were supportive, children were significantly more likely to demonstrate self-regulation and metacognition in child-initiated activity. Children's apparent perceptions of adult roles were crucial: in adult-initiated activities children appeared to cede control to adults. At the same time, adults played an important role for children, who were keen to display their knowledge to these significant people. Adults were particularly supportive of children's procedural knowledge. Practical implications include the importance of adult provision of and engagement in child-initiated activity, to afford them opportunities to observe and support children's self-regulation and metacognition and to maximise opportunities for children's autonomy and control.